2018
DOI: 10.1007/s11368-018-1993-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of mercury speciation in the coastal sediments

Abstract: Purpose Mercury speciation in sediments is linked to environmental conditions and processes. Domination of particular mercury species depends on its source, displays considerable seasonal behavior, and may be further modified due to oxygen levels, icing conditions, or the input of fresh organic matter. The purpose of this study was to examine the coastal area of the Gulf of Gdańsk in terms of mercury contamination and the influence of seasonal environmental changes on its speciation. Materials and methods In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…However, its potential to explore the sources of contamination on a beach surrounded by mines and industries is a new issue. The identification of mercury species in similar samples was already been carried out by using other methods of analysis [2,8,50], and in all cases the results were of great relevance from the environmental and social point of view. However, the HgTPD method entails some advantages when compared with X-ray absorption spectroscopy (EXAFS) and classic extraction methods, such as its low detection limit and high selectivity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, its potential to explore the sources of contamination on a beach surrounded by mines and industries is a new issue. The identification of mercury species in similar samples was already been carried out by using other methods of analysis [2,8,50], and in all cases the results were of great relevance from the environmental and social point of view. However, the HgTPD method entails some advantages when compared with X-ray absorption spectroscopy (EXAFS) and classic extraction methods, such as its low detection limit and high selectivity.…”
Section: Discussionmentioning
confidence: 95%
“…1 INDUROT, Campus de Mieres, Universidad de Oviedo, 33600 Mieres, Spain. 2 Instituto Nacional del Carbón (CSIC), Francisco Pintado Fe, 26, 33011 Oviedo, Spain.…”
Section: Supplementary Informationunclassified
“…The distribution pattern of Hg in the bottom sediment demonstrates that an expansion of the area occurs in relation to the area of distribution of Hg in the dry season [39]. Bełdowski et al [48] suggested that despite the decrease in mercury emissions to the environment in recent years, local weather conditions intensified by climate change seriously affect the bioavailability of past mercury deposits in coastal sediments. Indeed, global mineralization of the waters of the Aby lagoon caused by significant evaporation due to high temperatures during the dry season [22] [49] could explain this accumulation of mercury.…”
Section: Spatial Distribution Of Mercurymentioning
confidence: 99%
“…The theme of BSediment-water linkages in estuarine and marine environments: evaluating change in freshwater and saline habitats^is addressed by two papers. The contribution by Bełdowski et al (2018) explored the seasonal changes of mercury speciation in sediments in the coastal area of the Gulf of Gdańsk (Poland). The overall results suggested that although mercury emissions to the environment have decreased in recent years, local weather conditions, which may be intensified by climate change, seriously affect the bioavailability of past mercury deposits in coastal sediments.…”
mentioning
confidence: 99%